Some results associated with fractional integrals involving the extended Chebyshev functional - Dahmani, Zoubir (Acta Universitatis Apulensis, 2011)
n this paper, the Riemann-Liouville fractional integral is used to establish a new class of inequalities for the extended Chebyshev functional.